Il momento della trascrizione nel lavoro ecdotico (Quaderni di Gargnano, 2018)
In the field of epistolography, the tiring and always anxiety-inducing hunt for testimonial evidence culminates in the demanding but intellectually stimulating act of producing a critical edition of the work. The author focuses on the task of deciphering an idiography and considers the steps involved in producing a critical annotated edition from an archive work.
Keywords: idiografia; decifrazione; emendazione; edizione diplomatica; edizione filologica o umanistica